(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
Water erodes mountain systems made of hard rocks. When the water between the rocks freezes, it expands the cracks and cracks even the granite and basalts. Water slowly erodes the minerals contained in the rocks, dissolves them and carries them to the valleys. Nowadays, keeping water clean is one of the problems of serious concern to all mankind. What is the average amount of water needed for Uzbekistan per year? To answer this question, we will analyze the data on the use of water resources in various sectors of the economy in Uzbekistan